SYNTHESIS OF ADENOSINE MET-ENKAPHALIN CONJUGATE WITH EXPECTED BIOLOGICAL ACTIVITY - Shia, Jaafar S; Saour, Kawkab Y (Al-Nahrain Journal of Science, 2010)
In an effort for designing analogue with improved analgesic activity(opioid like activity) or mayposses added biological activities as antimetabolite with antineoplastic antibacterial and antiviral,etc., coupled bi natural metabolites (nucleoside peptides) are proposed in this study to synthesize1-deoxy-1-(6-amino-9-purinyl)-2,3-o-isopropylidene-B-D-ribfuranuronic acid amide with Tyr-Gly-Gly-Phe-Met-oH. In the hope that such combination have efficient transporting system acrossmembrane, natural penetration inside the cell and nucleus, represent an essential criteria forspecifically inducing the analagesic, antiviral, anticancer and also help for exploring other expectedbiological activities. The analogue was synthesized by applying the conventional solution methodand the coupling between peptide and nucleoside adenosine was carried out through amidelinkage.Confirmity of the synthetic procedure was achieved by applying different physico-chemicalanalyses including, thin layer chromatography (T.L.C) and melting point (M.P.), infraredspectroscopy (IR),elemental analysis(CHN analysis), optical rotation, amino acid analysis and NMR.